Recovery in Mind: A Recovery College's journey through the Covid‐19 pandemic. (25th October 2022) - Yoeli, Heather; Ryan, Angela; Hensby, Cath; Habermehl, Fiona; Burton, Sarah; Sin, Jacqueline
Abstract: Introduction: The Covid‐19 restrictions of 2020–2021 are known to have undermined the UK population's mental health. Working alongside staff, peer trainers and students at Recovery in Mind (RiM), a Recovery College (RC) in West Berkshire, England, this mixed‐methods study is amongst the first to investigate how an RC has responded to the pandemic. Methods: Working in co‐production with RiM staff and peer‐trainers, this study employed a mixed‐methods design, gathering Warwick‐Edinburgh Mental Wellbeing Scale (WEMWBS) well‐being outcome measures by questionnaire and student experience, learning and co‐production by interviews. Findings: This research found that RiM continued to produce demonstrable improvements in student mental health. Students welcomed the way that RiM adapted to offering online and socially distanced provisions. Students valued the skills that RiM taught and the way that RiM courses reinforced prior learning; above this, however, they valued the mutual support and sense of community that participation provided. Conclusion: This study underlines the value of RCs maintaining 'hidden curriculums' of peer support and community involvement. This research emphasizes co‐production as not only a tool for empowerment or service improvement but as a valuable skill for personal mental health recovery. Even when operating under the most unforeseen or challenging of conditions, RCs should always endeavour to prioritize and maintain co‐production. Patient or Public Contribution: In accordance with the RC ethos, this was an entirely co‐produced study, with academic researchers and RiM staff and peer trainers working democratically in partnership with one another to design and manage the study and to write up and disseminate findings. To ensure the independence and rigour of findings, data analysis was undertaken by external academic researchers.